PARTISIPASI MASYARAKAT DALAM PERENCANAAN TATA RUANG DAERAH UNTUK PEMBANGUNAN WILAYAH KOTA PADANG - Despica, Rika (Program Studi Pendidikan Geografi STKIP PGRI Sumatera Barat, 2014)
Climate and good performance in the construction needs to be executed, the characteristic is community participation, transparency, responsiveness and accountability. If this does not work together it will be a bottleneck in the development. With reference to the MPR IV / MPR / 2000 on recommendations in the Implementation of Regional Autonomy Policy, then the provision of opportunity for the public to actively participate in the implementation of development processes, including in the process of spatial planning. To realize the true public participation should be pursued. So cooperation with relevant parties such as universities, non-governmental organizations (NGOs), community leaders, parliamentarians, and other stakeholders need to be synergized. Strategies undertaken to improve the role of the community can be done by: 1) increasing awareness (Awareness Raising), 2) Advocacy Policy (Policy Advocacy), 3) Development Institutions (Institution Building), 4) Capacity (Capacity Building). Thus the community involvement in spatial planning becomes particularly relevant in the context of creating its territory, namely the layout in the public interest and create a beautiful environment